A domain decomposition method for quasi-incompressible formulations with discontinuous pressure field: Application to the mechanical study of a flexible bearing - Gosselet, Pierre; Rey, Christian; Léné, Françoise; Dasset, Pascal (European Journal of Computational Mechanics, 2002)
We study the implementation of a domain decomposition method for structures with quasi-incompressible components. We chose a mixed formulation where the pressure field is discontinuous on the interfaces between substructures. We propose an extension of classical preconditioners to this class of problems. The numerical simulation of the mechanical behaviour of the flexible bearing of the nozzle of a solid propellant booster is then conducted using various Newton-Krylov parallel approaches. We present the main mechanical results and compare the numerical performance of the parallel approaches to a sequential approach.